Penggunaan Metode Student Team Achievement Division untuk Meningkatkan Motivasi Belajar Siswa pada Konsep Menghitung Luas Segitiga Kelas IV SD - Rodinah Rodinah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The purpose of this study was (1) to analyze the impact of using the Student Team Achievement Division (STAD) method to increase student motivation about the concept of calculating the area of a triangle in class IV SD Negeri 1 Dermaji, Lumbir District, Banyumas Regency. (2) analyzing the impact of using the Student Team Achievement Division (STAD) method can improve student learning outcomes about the concept of calculating the area of a triangle in class IV SD Negeri 1 Dermaji Banyumas District Banyumas Regency. The CAR procedure consists of four steps of research, namely planning, implementation, observation and reflection in its implementation of two cycles. The results of this study can be concluded as follows: (1) the use of the STAD method in mathematics learning about calculating the area of a triangle can increase learning motivation of fourth grade students of SD Negeri 1 Dermaji Banyumas District Banyumas Regency with an increase from 10 students to 22 students or 50.00%. (2) With the use of visual aids can improve student learning outcomes in class IV SD Negeri 1 Dermajid with an average from the beginning of learning to the second cycle that is 49.79 to 75.63 increased 86.67 and mastery learning from 8 students to 18 students later rose to 23 students from 24 students overall. So in the conclusion of this study are (1) The use of the STAD method can increase student motivation in class IV SD Negeri 1 Dermaji Banyumas District Banyumas Regency; (2) The use of the STAD method is proven to be able to improve student learning outcomes in class IV SD Negeri 1 Dermaji, Banyumas District, Banyumas Regency.